Adaptation of the human nervous system for self-aware secure mobile and IoT systems - Thanigaivelan, Nanda Kumar (fi=Turun yliopisto|en=University of Turku|, 2023)
IT systems have been deployed across several domains, such as hospitals and industries, for the management of information and operations. These systems will soon be ubiquitous in every field due to the transition towards the Internet of Things (IoT). The IoT brings devices with sensory functions into IT systems through the process of internetworking. The sensory functions of IoT enable them to generate and process information automatically, either without human contribution or having the least human interaction possible aside from the information and operations management tasks. Security is crucial as it prevents system exploitation. Security has been employed after system implementation, and has rarely been considered as a part of the system. In this dissertation, a novel solution based on a biological approach is presented to embed security as an inalienable part of the system. The proposed solution, in the form of a prototype of the system, is based on the functions of the human nervous system (HNS) in protecting its host from the impacts caused by external or internal changes. The contributions of this work are the derivation of a new system architecture from HNS functionalities and experiments that prove the implementation feasibility and efficiency of the proposed HNS-based architecture through prototype development and evaluation. The first contribution of this work is the adaptation of human nervous system functions to propose a new architecture for IT systems security. The major organs and functions of the HNS are investigated and critical areas are identified for the adaptation process. Several individual system components with similar functions to the HNS are created and grouped to form individual subsystems. The relationship between these components is established in a similar way as in the HNS, resulting in a new system architecture that includes security as a core component. The adapted HNS-based system architecture is employed in two the experiments prove its implementation capability, enhancement of security, and overall system operations. The second contribution is the implementation of the proposed HNS-based security solution in the IoT test-bed. A temperature-monitoring application with an intrusion detection system (IDS) based on the proposed HNS architecture is implemented as part of the test-bed experiment. Contiki OS is used for implementation, and the 6LoWPAN stack is modified during the development process. The application, together with the IDS, has a brain subsystem (BrSS), a spinal cord subsystem (SCSS), and other functions similar to the HNS whose names are changed. The HNS functions are shared between an edge router and resource-constrained devices (RCDs) during implementation. The experiment is evaluated in both test-bed and simulation environments. Zolertia Z1 nodes are used to form a 6LoWPAN network, and an edge router is created by combining Pandaboard and Z1 node for a test-bed setup. Two networks with different numbers of sensor nodes are used as simulation environments in the Cooja simulator. The third contribution of this dissertation is the implementation of the proposed HNS-based architecture in the mobile platform. In this phase, the Android operating system (OS) is selected for experimentation, and the proposed HNS-based architecture is specifically tailored for Android. A context-based dynamically reconfigurable access control system (CoDRA) is developed based on the principles of the refined HNS architecture. CoDRA is implemented through customization of Android OS and evaluated under real-time usage conditions in test-bed environments. During the evaluation, the implemented prototype mimicked the nature of the HNS in securing the application under threat with negligible resource requirements and solved the problems in existing approaches by embedding security within the system. Furthermore, the results of the experiments highlighted the retention of HNS functions after refinement for different IT application areas, especially the IoT, due to its resource-constrained nature, and the implementable capability of our proposed HNS architecture.

--- IT-järjestelmiä hyödynnetään tiedon ja toimintojen hallinnassa useilla aloilla, kuten sairaaloissa ja teollisuudessa. Siirtyminen kohti esineiden Internetiä (Internet of Things, IoT) tuo tällaiset laitteet yhä kiinteämmäksi osaksi jokapäiväistä elämää. IT-järjestelmiin liitettyjen IoT-laitteiden sensoritoiminnot mahdollistavat tiedon automaattisen havainnoinnin ja käsittelyn osana suurempaa järjestelmää jopa täysin ilman ihmisen myötävaikutusta, poislukien mahdolliset ylläpito- ja hallintatoimenpiteet. Turvallisuus on ratkaisevan tärkeää IT-järjestelmien luvattoman käytön estämiseksi. Valitettavan usein järjestelmäsuunnittelussa turvallisuus ei ole osana ydinsuunnitteluprosessia, vaan otetaan huomioon vasta käyttöönoton jälkeen. Tässä väitöskirjassa esitellään uudenlainen biologiseen lähestymistapaan perustuva ratkaisu, jolla turvallisuus voidaan sisällyttää erottamattomaksi osaksi järjestelmää. Ehdotettu prototyyppiratkaisu perustuu ihmisen hermoston toimintaan tilanteessa, jossa se suojelee isäntäänsä ulkoisten tai sisäisten muutosten vaikutuksilta. Tämän työn keskeiset tulokset ovat uuden järjestelmäarkkitehtuurin johtaminen ihmisen hermoston toimintaperiaatteesta sekä tällaisen järjestelmän toteutettavuuden ja tehokkuuden arviointi kokeellisen prototyypin kehittämisen ja toiminnan arvioinnin avulla. Tämän väitöskirjan ensimmäinen kontribuutio on ihmisen hermoston toimintoihin perustuva IT-järjestelmäarkkitehtuuri. Tutkimuksessa arvioidaan ihmisen hermoston toimintaa ja tunnistetaan keskeiset toiminnot ja toiminnallisuudet, jotka mall-innetaan osaksi kehitettävää järjestelmää luomalla näitä vastaavat järjestelmäkomponentit. Nä-istä kootaan toiminnallisuudeltaan hermostoa vastaavat osajärjestelmät, joiden keskinäinen toiminta mallintaa ihmisen hermoston toimintaa. Näin luodaan arkkitehtuuri, jonka keskeisenä komponenttina on turvallisuus. Tämän pohjalta toteutetaan kaksi prototyyppijärjestelmää, joiden avulla arvioidaan arkkitehtuurin toteutuskelpoisuutta, turvallisuutta sekä toimintakykyä. Toinen kontribuutio on esitetyn hermostopohjaisen turvallisuusratkaisun toteuttaminen IoT-testialustalla. Kehitettyyn arkkitehtuuriin perustuva ja tunkeutumisen estojärjestelmän (intrusion detection system, IDS) sisältävä lämpötilan seurantasovellus toteutetaan käyttäen Contiki OS -käytöjärjestelmää. 6LoWPAN protokollapinoa muokataan tarpeen mukaan kehitysprosessin aikana. IDS:n lisäksi sovellukseen kuuluu aivo-osajärjestelmä (Brain subsystem, BrSS), selkäydinosajärjestelmä (Spinal cord subsystem, SCSS), sekä muita hermoston kaltaisia toimintoja. Nämä toiminnot jaetaan reunareitittimen ja resurssirajoitteisten laitteiden kesken. Tuloksia arvioidaan sekä simulaatioiden että testialustan tulosten perusteella. Testialustaa varten 6LoWPAN verkon toteutukseen valittiin Zolertia Z1 ja reunareititin on toteutettu Pandaboardin ja Z1:n yhdistelmällä. Cooja-simulaattorissa käytettiin mallinnukseen ymp-äristönä kahta erillistä ja erikokoisuta sensoriverkkoa. Kolmas tämän väitöskirjan kontribuutio on kehitetyn hermostopohjaisen arkkitehtuurin toteuttaminen mobiilialustassa. Toteutuksen alustaksi valitaan Android-käyttöjärjestelmä, ja kehitetty arkkitehtuuri räätälöidään Androidille. Tuloksena on kontekstipohjainen dynaamisesti uudelleen konfiguroitava pääsynvalvontajärjestelmä (context-based dynamically reconfigurable access control system, CoDRA). CoDRA toteutetaan mukauttamalla Androidin käyttöjärjestelmää ja toteutuksen toimivuutta arvioidaan reaaliaikaisissa käyttöolosuhteissa testialustaympäristöissä. Toteutusta arvioitaessa havaittiin, että kehitetty prototyyppi jäljitteli ihmishermoston toimintaa kohdesovelluksen suojaamisessa, suoriutui tehtävästään vähäisillä resurssivaatimuksilla ja onnistui sisällyttämään turvallisuuden järjestelmän ydintoimintoihin. Tulokset osoittivat, että tämän tyyppinen järjestelmä on toteutettavissa sekä sen, että järjestelmän hermostonkaltainen toiminnallisuus säilyy siirryttäessä sovellusalueelta toiselle, erityisesti resursseiltaan rajoittuneissa IoT-järjestelmissä.